Strategi Peningkatan Kapasitas Usaha Mikro dan Kecil Di Masa Pandemi Dalam Pembangunan Ekonomi Digital Di Indonesia - Eka Travilita Oktaria (Universitas Bandar Lampung (UBL), 2021)
Indonesia experienced an economic recession at the end of 2020 the COVID-19 which caused many micro and small businesses to have to stop their business activities due to various factors. The impact that is felt is that many micro and small businesses have to make policies to reduce workforce because of the sharp decline in turnover. In addition, the imposition of large-scale social restrictions starting in early 2020 or the first quarter has a very dominant effect. Given that economic activity is still in the micro business sector, with the existence of social restrictions, the impact felt by economic actors in several regions throughout the archipelago is an obstacle for micro and small business actors to be able to increase their business during a pandemic like this. Difficulty conditions require business actors to continue to survive by utilizing technological aspects to be able to carry out economic activities as usual. The shift in human habits to use digital technology during a pandemic has made business actors also have to be able to transform digitally to be able to improve their business as before.